STUDI EKSPLORASI KUALIFIKASI DAN KOMPETENSI GURU BIDANG STUDI BIOLOGI SMP—SMA SEBAGAI BASIS PROGRAM PENINGKATAN KUALITAS PENDIDIKAN - Marten Masoka; Ibrohim Ibrohim; Sri Endah Indriwati (Graduate School of Universitas Negeri Malang, 2017)
The study has been carried out aiming to (1) describe the qualifications of teachers of biology majors IPA/at the level of junior high/high school in Bintuni straits. (2) describe the professional and pedagogic competence Biology teachers in junior/senior high school. (3) describe the problems and needs of teachers of Biology for developing junior/senior high school teachers komptensi in the bay of bintuni straits. this research is a descriptive exploratory study types. the subject of this research is the field of study teacher ipa/biology in junior high/high school education unit and the object of the research is the qualification, competence and field of study teacher needs Biology. data about the qualifications, the competence and the need for teachers to be analyzed in qualitative, descriptive, i.e. with make, average (procentated). The results showed that educational qualifications teachers of SCIENCE/biology as a whole on the junior level or high school reached 95.2% is a strata (S1) of 21 teachers response and 4.8% qualified diploma (D3). Alignment of academic qualification with majors in SCIENCE/biology taught at junior high school-education unit is 71% while not appropriate(mismatched) 29%. While the Biology teacher in high school or junior high school level master professional competence 44.5% and pedagogic competence competence which controlled 30,7%.Penelitan ini bertujuan untuk (1) mendeskripsikan kualifikasi guru bidang studi Biologi pada tingkat SMP/SMA di Kabupaten Teluk Bintuni; (2) mendeskripsikan kompetensi profesional dan pedagogik guru Biologi SMP/SMA; (3) mendeskripsikan permasalahan dan kebutuhan guru Biologi untuk mengembangkan komptensi guru SMP/SMA di Kabupaten Teluk Bintuni. Penelitian ini merupakan penelitian deskriptif eksploratif. Subjek penelitian ini adalah guru bidang studi Biologi pada satuan pendidikan SMP/SMA dan objek penelitian ini adalah kualifikasi, kompetensi serta kebutuhan guru bidang studi Biologi. Data tentang kualifikasi, kompetensi dan kebutuhan guru dianalisis secara deskriptif kualitatif, yakni dengan menjumlah dan merata-rata. Hasil penelitian menunjukkan bahwa kualifikasi pendidikan guru Biologi secara keseluruhan pada tingkat SMP maupun SMA mencapai 95,2% adalah strata satu (S1) dari 21 guru yang terdata dan 4,8% berkualifikasi diploma (D3). Kesesuaian antara kualifikasi akademik dengan bidang studi Biologi yang diajarkan pada satuan pendidikan SMP-SMA sebesar 71% dan yang tidak sesuai sebesar 29%. Sementara itu, guru Biologi pada tingkat SMP maupun SMA yang menguasai kompetensi profesional 44,5% dan kompetensi pedagogik 30,7%.